Forensic psychiatry in Kuwait - characterization of forensic psychiatry patients evaluated over year duration in the only available forensic psychiatry unit. (September 2018) - Alhumoud, Abdulmohsen; Zahid, Muhammad; Ibrahim, Sameh; Syed, Talal; Naguy, Ahmed
Abstract: Introduction: The offending behavior arising from a mental disorder invokes criminal responsibility doctrines or insanity defenses and calls for legislative framework ensuring availability of care and treatment for the patient and protection of the public from harm from the offender. The conviction of mentally disordered offenders varies depending upon the local legislation and its socio-cultural context, so do the principles, procedures and guidelines for forensic assessments between different countries. The criminal Act of Kuwait, which governs the work of forensic psychiatrists remain unchanged, from a psychiatric point of view, since it was enacted in the early 1960's. Objectives: To shed some light on the forensic psychiatry services running in Kuwait and describe forensic psychiatry patients evaluated in the only-available forensic psychiatry unit. Methods: Retrospective chart review of all cases referred for criminal forensic psychiatric assessments during the period from January 1st, 2016 to May 31st, 2017. The demographics, types of offences, psychiatric diagnoses, and details of psychiatric evaluations were retrieved and characterized. Results: A total of 95 case-notes were reviewed. Most of them were males (90%), Kuwaiti nationals (77%), primary or intermediate school education (74%), and were aged 20–39 (69%). Almost all (97%) of the referrals required ascertainment of 'responsibility' for the alleged offence. Eighty-six percent (N = 81) of the offenders were referred from the police or the public prosecutor office. Eighty-three percent (N = 79) of the offenders were found to have a mental disorder while 55% (N = 52) were found to be criminally responsible. The males (57%) outnumbered the females (33%) as criminally responsible. Conclusions: The number of mentally ill offenders referred for criminal responsibility and fitness to stand trial is very small compared to western countries. One reason behind this could be that a substantial number of the mentally disordered offenders pass undetected through the legal system. It is then incumbent that psychiatrists and forensic mental health workers might need to provide better awareness and education about mental health to legal authorities in Kuwait.